2018
DOI: 10.1148/radiol.2018180318
|View full text |Cite
|
Sign up to set email alerts
|

Acute Appendicitis: A Meta-Analysis of the Diagnostic Accuracy of US, CT, and MRI as Second-Line Imaging Tests after an Initial US

Abstract: Purpose To evaluate the sensitivity, specificity, and diagnostic odds ratios of US, CT, and MRI as second-line imaging modalities after initial US for assessing acute appendicitis in children and adults. Materials and Methods A literature search was conducted in Medline and Embase to identify articles that used surgery or histopathologic examination alone or in combination with clinical follow-up or chart review to evaluate the diagnostic accuracy of second-line imaging modalities. The quality of articles was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 87 publications
(101 reference statements)
2
59
1
3
Order By: Relevance
“…Single-shot T 2 WI sequences such as HASTE are widely used to assess patients with acute abdominal pain because these sequences can obtain images in the lower abdominal region for approximately 20 s with few motion artifacts due to vascular pulsation, respiratory motion, and bowel peristalsis because single-shot T 2 WI with one radiofrequency excitation pulse generates a long train of spin echoes. 9,12 However, its spatial resolution is lower than that of turbo spin echo T 2 WI because of blurring, especially in small structures possessing a short T 2 relaxation time. [31][32][33] Therefore, single-shot T 2 WI is appropriate for evaluating anatomical structures, but it is not suitable for assessing subtle changes of signal intensity.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-shot T 2 WI sequences such as HASTE are widely used to assess patients with acute abdominal pain because these sequences can obtain images in the lower abdominal region for approximately 20 s with few motion artifacts due to vascular pulsation, respiratory motion, and bowel peristalsis because single-shot T 2 WI with one radiofrequency excitation pulse generates a long train of spin echoes. 9,12 However, its spatial resolution is lower than that of turbo spin echo T 2 WI because of blurring, especially in small structures possessing a short T 2 relaxation time. [31][32][33] Therefore, single-shot T 2 WI is appropriate for evaluating anatomical structures, but it is not suitable for assessing subtle changes of signal intensity.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
“…6 Consequently, MRI is recommended for acute abdominal pain in pregnant patients. 7,8 The use of MRI in patients with acute abdominal pain was previously limited to patients with biliary and gynecological disease that could not be diagnosed using CT; however, several studies reported that MRI is helpful for diagnosing acute abdominal pain caused by not only acute appendicitis [9][10][11][12] but also other diseases. [13][14][15] MRI has potentially high-contrast resolution, and it can illuminate ischemic changes caused by acute mesenteric ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…16 Although various studies have documented validity of CT against higher AS, 17 however, only a few have emphasized upon its prime utility in patients with low AS or equivocal cases that may end up in having aetiologies other than acute appendicitis. 18 Prompt identification of an alternate diagnosis in such patients is strategic not only to reduce patient anxiety and hospital stay but also to guide clinicians towards specific treatment and avoid negative surgery (appendectomy). Therefore, we aim to highlight usefulness of CT imaging in such stratum of patients (i.e., with clinical suspicion of acute appendicitis and equivocal AS).…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…The meta-analysis by Eng et al (10) included 37 studies and evaluated a relevant number of patients: 717 patients with US examinations, 2525 patients with CT examinations, and 714 patients with MRI. The authors concluded that second-line US, CT, and MRI have comparable and high accuracy in helping to diagnose appendicitis in children, adults, and pregnant women after an initial US examination with negative or inconclusive results.…”
mentioning
confidence: 99%
“…The value of a meta-analysis depends on the methodologic process, quality of the included studies, and of the assessment of the studies' heterogeneity. Eng et al (10) followed rigorous methods for study analysis and inclusion criteria on the basis of the recommendations from the Preferred Reporting Items for Systematic Reviews and Meta-analyses. The authors included only studies that focused on the evaluation of diagnostic accuracy of a second-line US, CT, or MRI after an initial US.…”
mentioning
confidence: 99%